2004
DOI: 10.1111/j.1365-2672.2004.02173.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of atypical Erwinia carotovora strains causing blackleg of potato in Brazil

Abstract: Aims: To determine the characteristics of bacteria associated with the blackleg disease of potato in Brazil and compare them with species and subspecies of pectolytic Erwinia. Methods and Results: Biochemical and physiological characteristics of 16 strains from blackleg-infected potatoes in State of Rio Grande do Sul, Brazil, were determined and differentiated them from all the E. carotovora subspecies and E. chrysanthemi. Pathogenicity and maceration ability of the Brazilian strains were greater than those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
184
0
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(203 citation statements)
references
References 21 publications
4
184
0
15
Order By: Relevance
“…The two P. betavasculorum strains, B20 and B22, were positive for utilization of Tween-80 and N-acetyl-D-glucosamine in the Biolog tests, distinguishing them from E. carotovora subsp. brasiliensis (10).…”
Section: Resultsmentioning
confidence: 99%
“…The two P. betavasculorum strains, B20 and B22, were positive for utilization of Tween-80 and N-acetyl-D-glucosamine in the Biolog tests, distinguishing them from E. carotovora subsp. brasiliensis (10).…”
Section: Resultsmentioning
confidence: 99%
“…The predominance of Ech (89.8%) causing soft rot in arracacha roots in Brazil is a novel finding, since previous papers reporting the disease considered Ecc as the predominant one (Romeiro et al, 1988;Lopes & Quezado-Soares, 1997), although based on the identification of few isolates. Lately, Oliveira et al (2003) described Eca (55%) and Ecc (44%) as the predominant subspecies in potato fields in Southern Brazil, which was unexpected, and more recently, Duarte et al (2004) reported a new, atypical potato blackleg strain called E. carotovora subsp. brasiliensis.…”
mentioning
confidence: 99%
“…Recently, atypical strains causing blackleg of potato in Southern Brazil were proposed as a new subspecies (E. carotovora subsp. brasiliensis) by Duarte et al (2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further characterisation of these aggressive isolates using PCR assays to distinguish Pcc from P. carotovorum subsp. brasiliensis (Pbr) was carried out using primers EXPCCF and EXPCCR (Kang et al, 2003) and Br1f and L1r (Duarte et al, 2004), respectively. From 18 isolates, occurring throughout the four major growing localities (Fig.…”
mentioning
confidence: 99%